PENGARUH GREEN MARKETING DAN IKLAN DIGITAL TERHADAP MINAT BELI KONSUMEN PRODUK AQUA (STUDI KASUS KONSUMEN PRODUK AQUA DI MEDAN MALL) - Syeh Aditya Maulana; Hesti Sabrina (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine the effect of green marketing and digital advertising on buying interest in Aqua products at Medan Mall. This type of research uses quantitative methods. The population of this study cannot be calculated, therefore using the Cochran formula, the sample used was 96 respondents. The results obtained from this study are partially green marketing (X1) has a positive and significant effect on purchase intention, with a tcount value of 2.002 greater than the ttable 1.985 and the significance value is 0.048 0.05. Simultaneously, green marketing variables (XI) and digital advertising (X2) have a positive and significant effect on purchase intention (Y) of Aqua products at Medan Mall with a value of Fcount (3.960) > Ftable (3.09) and the significance value is 0.02